PENGARUH BIAYA OVERHEAD PABRIK TERHADAP HARGA POKOK PRODUKSI PADA CV. TIRTA MEKAR JAYA - Luki Sri Anggorowati; alean kistiani; unna ria (Universitas Boyolali, 2019)
Cost accounting can help management to obtain the production costs required in data processing in accordance with accounting theory and principles, so it can also be used to determine the cost of the right production. The purpose of this research is to know the effect of fixed and fixed factory overhead cost to the cost of production in CV Tirta Mekar Jaya, and to compare the cost of production using the application of factory overhead cost using full costing method with the determination of cost of goods manufactured by company. This research is a quantitative descriptive research where the calculation with numbers is estimated more objective because to determine the conclusion that will be obtained with this research. The data obtained in the study are primary data and secondary data. Secondary data is obtained from cost data that is processed and presented by the company and the literature.The results of the research indicate among others: 1) there are some components of overhead costs that have not been taken into account by the CV. Tirta Mekar Jaya ie indirect labor cost in Group fixed factory overhead cost, gallon usage cost, depreciation cost of production equipment, maintenance and maintenance cost of building, machine and production equipment at group overhead cost group is not fixed. 2) BOP contribution on gallon product by 22.93%, 6.49% for bottle products and 9.09% glass products. BOP still has a considerable effect on gallon products but less %. BOP remains sufficiently influential on gallon products but has little effect on bottle products and glass products. 3) The contribution of fixed BOP on gallon, bottle and glass products are 34.34%, 90.84% ​​and 84.06% respectively. BOP is not fixed enough to affect gallon products and greatly affect the bottle and glass products.